Dasar Pendidikan Moral Anak Usia Dini: Perintah dan Larangan dalam Qur’an Surat Lukman Ayat 13-19 - Suminah Suminah; Fauzi Fauzi (Malewa: Journal of Multidisciplinary Educational Research, 2025)
Early Childhood Education (PAUD) serves as the primary foundation for developing children’s personality and moral character during the golden age (0–6 years). At this stage, children are highly sensitive to habits, modeling, and moral stimulation. This paper aims to examine the relevance of the Qur’anic concepts of commands (amr) and prohibitions (nahy) in Surah Luqman verses 13–19 as the basis for moral education in early childhood. The study employs a library research method by analyzing classical tafsir, relevant literature, and contemporary studies on Islamic character education. The findings reveal that these verses contain comprehensive moral principles, including the prohibition of polytheism, commands to honor parents, awareness of divine supervision, prayer, amar ma’ruf nahi munkar (enjoining good and forbidding evil), patience, and humility. These values create a balance between theological, ethical, and psychological aspects in children’s moral development. Implementation in PAUD can be achieved through habituation, exemplary behavior, daily worship, and integration of Qur’anic values into learning activities. Qur’an-based moral education prepares children to be virtuous, disciplined, and responsible individuals capable of facing modern challenges. Therefore, Surah Luqman verses 13–19 serve as a strategic guideline for nurturing Islamic character in early childhood.